Determination of Suitability Test on Digital Mammography Using Voltage Accuracy Parameter - Fitriani Fitriani; Muhammad Yunus; Muh Fachrul Latief; A Indra Wulan Sari Ramadani; Meilan Demulawa; Haris Munandar; Muh. Nur Akbar (Akademi Teknologi Industri Dewantara Palopo, 2021)
Determination of suitability test on digital mammography have been conducted from 2016-2018 at a hospital in Makassar City using voltage accuracy parameter. This measurement was used detector, and X-ray multimeter. Statistically, voltage accuracy parameter has correlation value, r = 0.866 (perfect correlation). While the p value obtained in voltage accuracy parameter is p < 0.05. There are significant differences in value from 2016-2018. The result of the suitability test for voltage accuracy parameter is still within the tolerance limit as recommended by the IAEA.